2008
DOI: 10.4049/jimmunol.181.2.891
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Expression of the Bovine Leukemia Virus-Binding Receptor on B and T Lymphocytes Is Induced by Receptor Engagement

Abstract: Bovine leukemia virus (BLV), one of the most common infectious viruses of cattle, is endemic in many herds. Approximately 30–40% of adult cows in the United States are infected by this oncogenic C-type retrovirus and 1–5% of animals will eventually develop a malignant lymphoma. BLV, like the human and simian T cell leukemia viruses, is a deltaretrovirus but, in contrast with the latter, the BLV receptor remains unidentified. In this study, we demonstrate that the amino-terminal 182 residues of the BLV envelope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Studies by other groups clearly established that neutrophils are avid consumers of glucose (40) and that the upregulation of surface Glut1 expression is associated with neutrophil activation upon exposure to inflammatory conditions (41). A similar increase in glucose-dependent metabolism is seen in other activated leukocyte subsets, notably T and B cells (29,(42)(43)(44)(45). In contrast with Glut1, expression of the amino acid transporter ASCT2 is not uniformly increased on CF airway neutrophils (decreased on A1 and increased on A2 neutrophils compared with blood neutrophils, respectively).…”
Section: Discussionmentioning
confidence: 67%
“…Studies by other groups clearly established that neutrophils are avid consumers of glucose (40) and that the upregulation of surface Glut1 expression is associated with neutrophil activation upon exposure to inflammatory conditions (41). A similar increase in glucose-dependent metabolism is seen in other activated leukocyte subsets, notably T and B cells (29,(42)(43)(44)(45). In contrast with Glut1, expression of the amino acid transporter ASCT2 is not uniformly increased on CF airway neutrophils (decreased on A1 and increased on A2 neutrophils compared with blood neutrophils, respectively).…”
Section: Discussionmentioning
confidence: 67%
“…A previous report used the BLV envelope (ENV) receptor binding domain showed that BLV receptor molecules are expressed by pro/pre B cells (but not by mature/arrested B cells), by activated B and T cells (but not by arrested B and T cells), by human thymus cells induced by IL-7, and by proliferating lymphocytes [25]. CD4, CD8, and CD5 - IgM + B cells proliferate in an antigen-specific manner; however, CD5 + IgM + B cells can proliferate in the absence of antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Although BLV primarily infects B cells, it can infect other cell types (Lavanya et al, 2008), although this is rare. Even without direct infection of other immune cells, BLV infection not only impacts B cell function but also the function of other immune cells, particularly T cells.…”
Section: T Cell Abnormalitiesmentioning
confidence: 99%